Fiscal Governance and Government Investment in Europe since the 1990s - Hans Pitlik (Austrian Institute of Economic Research (WIFO), 2010)
Stringent fiscal rules and budgetary procedures might generate incentives for political decision-makers to cut predominantly productive public investment during periods of fiscal consolidation. While the influence of the European Stability and Growth Pact on public investment received a lot of attention in the empirical literature, only a few studies consider the impact of different budgetary decision-making rules and procedures at the national level on government investment spending. We test empirically for the effect of political factors and the institutional framework of budgeting on public investment in EU 15 over the period 1990-2005. Our results show that stringent quantitative constraints limit government investment, but a centralisation of budgeting procedures by providing more agenda setting powers to the finance minister (delegation approach) or by the use of medium-term fiscal contracts are not related to public investment spending cuts.
Keywords: 330; fiscal consolidation fiscal policy; Finanzpolitik; Regelbindung versus Diskretion; Öffentliche Investition; EU-Staaten